Bitumen stabilized ballast: A potential solution for railway track-bed. (15th October 2016) - D'Angelo, Giacomo; Thom, Nicholas; Lo Presti, Davide
Graphical abstract: Highlights: Bitumen stabilized ballast (BSB) as new solution to improve track-bed performance. Laboratory study to evaluate BSB potential for clean and fouled ballast. Significant reduction in permanent deformation and deformation rate. Modified mechanical characteristics of ballast layer. Abstract: Railway ballast degradation under dynamic loads progressively leads to loss of mechanical performance and geometry of the track, so that maintenance interventions are frequently needed. In order to systematically avoid this issue, recently solutions have been proposed to reinforce track-bed by using polyurethane and/or resins as well as asphalt layers among others. Nonetheless, their main limitations are related to the high initial cost and low productivity. To cope with these limitations, in this study, bitumen stabilized ballast (BSB) is proposed as a new solution for ballast stabilization. This method aims at improving durability and reducing settlement by modifying both stiffness and the ability of energy dissipation of the layer. The paper introduces the potential of this technology as material to be used in railway track-beds by presenting the results of a laboratory-based investigation using the Precision Unbound Material Analyser (PUMA). Different variables such as ballast grading, bitumen emulsion dosage, compaction method and stress levels are considered. Results showed a significant decrease in permanent deformation and deformation rate associated with modified stiffness and energy dissipation properties of BSB, which suggest the potential for improving long-term performance and sustainability of ballasted track.